Rings and Modules Whose Socles are Relative Ejective - Nuray Eroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Lifting homomorphism from modulesto modules or even from certain submodule to the modules have been importantboth in ring and module theory. In this note we study rings and modules whosesocles are relative ejective. Moreover we reduce our consideration to rings andmodules with injective socles which provides the dual notion to PSmodules.